Analisis Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Pupuk Anorganik (Kasus : Desa Srimulyo Dan Sukodono, Kecamatan Dampit) - Anggara, Muhammad Rafi; Ibrahim, Jabal Tarik; Mazwan, M. Zul (Forum Agribisnis, 2024)
Inorganic fertilizers are currently still widely used and are the main choice for farmers because they can increase crop productivity. Companies need to pay attention to consumer orientation, which is related to how to find the target market, needs and convince consumers to make a purchase. This study aims to analyze the influence of brand image, price, review, ecology, and credibility on the decision to purchase inorganic fertilizers by coffee farmers. The locations taken are Srimulyo and Sukodono villages, Dampit District, considering that the village is the largest coffee-producing village in Malang. Purposive sampling was used for sampling as many as 35 coffee farmers with the provision of using and purchasing inorganic fertilizers. The data used in the study is primary data collected through surveys with observations, interviews, questionnaires and documentation. The research uses SEM (Structural Equation Modelling) data analysis with the PLS (Partial Least Square) approach, and conducts data analysis with the help of SmartPLS 4.0 software. The results of the analysis of respondent characteristics showed that most coffee farmers were dominated by men and the level of education of farmers varied from elementary to bachelor's degree. Most of the respondents' farming experience was from 1 to 50 years with a maximum land area of 2 ha. Testing the inner model obtained a determination coefficient (R-Square) of 60.1% brand image, price, reviews, ecology, and credibility were able to explain the influence on the decision to purchase inorganic fertilizers by farmers. The results of bootstrapping data showed that brand image and ecological had a significant negative effect and reviews had a significant positive effect on the decision to purchase inorganic fertilizers. Factors that do not affect the decision to buy inorganic fertilizers are price and credibility.